Global corporate responsibility disclosure: A comparative analysis of field, national, and global influences. (January 2017) - Lim, Alwyn
In the domain of global corporate responsibility (GCR), international organizations have promoted disclosure as a means to address global concerns with corporations' social and environmental practices. Business disclosure practices, however, remain uneven across organizations and countries. This article examines various field, national, and global factors that facilitate or mitigate GCR disclosure among corporations worldwide. Analyzing unique quantitative data on more than 1800 disclosure reports by corporations in more than 50 countries, this article presents two main findings. First, field-level factors are prominent but they influence disclosure levels in different ways. Third-party verification encourages greater disclosure, while peer organizations mitigate disclosure. Second, national and global factors influence disclosure differently in developed and developing countries. Business disclosure in developed countries is impacted by national factors while, in developing countries, disclosure is significantly influenced by global factors. The article concludes by discussing the implications of GCR disclosure for wider global corporate governance concerns.